Analysis of Potential and Strategy for Green Human Resource - Indra Krishernawan; Sugeng Karyadi; Ahmad Junaidi; Dennis Lorens; Maulana Sani (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Human resources play a key role in every organizational activity. As a key factor, human resources determine the success of organizational activities. The demand for organizations to acquire, develop, and retain quality human resources is increasingly pressing in line with the ever-changing dynamics of the environment. The purpose of this study is to analyze the concept of potential and strategy for green human resource. To understand and simplify the analysis of the concept of potential and strategy for green human resources, a qualitative approach based on a literature review was conducted. To aid explanation in qualitative approaches and literature reviews, secondary data is needed. Research results show that green human resources have potential for job creation, sustainable economic growth, improved organizational performance, innovation and efficiency, and reputation enhancement. The strategy to realize this potential is to improve workforce readiness through green human resource management training and green human resource management practices.